Analysis of the Involvement of the Isoleucine Biosynthesis Pathway in Photoheterotrophic Metabolism of Rhodospirillum rubrum - Bayon-Vicente, Guillaume; Marchand, Elie; Ducrotois, Jeson; Dufrasne, François E.; Hallez, Regis; Wattiez, Ruddy; Leroy, Baptiste (Frontiers in Microbiology, 2021)
Purple non-sulfur bacteria (PNSB) are recognized as a highly versatile group of bacteria that assimilate a broad range of carbon sources. Growing heterotrophically, PNSB such as Rhodospirillum rubrum (Rs. rubrum) generate reduced equivalents that are used for biomass production. However, under photoheterotrophic conditions, more reduced electron carriers than required to produce biomass are generated. The excess of reduced equivalents still needs to be oxidized for the metabolism to optimally operate. These metabolic reactions are known as electron sinks. Most PNSB rely on the CO2-fixing Calvin cycle and H2 production to oxidize these reduced equivalents. In addition to these well-described electron sinks, the involvement of some pathways, such as polyhydroxyalkanoate (PHA) biosynthesis, in redox poise is still controversial and requires further studies. Among them, isoleucine biosynthesis has been recently highlighted as one of these potential pathways. Here, we explore the role of isoleucine biosynthesis in Rs. rubrum. Our results demonstrate that the isoleucine content is higher under illuminated conditions and that submitting Rs. rubrum to light stress further increases this phenomenon. Moreover, we explore the production of (p)ppGpp in Rs. rubrum and its potential link with light stress. We further demonstrate that a fully functional isoleucine biosynthesis pathway could be an important feature for the onset of Rs. rubrum growth under photoheterotrophic conditions even in the presence of an exogenous isoleucine source. Altogether, our data suggest that isoleucine biosynthesis could play a key role in redox homeostasis.